Histopathological Diagnosis of Diseases Affecting Amphibians Inhabiting Kihansi Gorge, Tanzania - Malago, Joshua J (Tanzania Journal of Science, 2019)
Kihansi gorge is a natural habitat to Kihansi spray toad (KST), Nectophrynoides asperginis. The toad is extinct in its natural habitat partly due to diseases. Efforts to successfully re-introduce it are primed by awareness and mitigation of prevalent diseases at the gorge. This study aimed at exploring the prevalent amphibian diseases at and around Kihansi gorge. A total of 182 individuals from Petropedetes yakusini (n = 60), Nectophrynoides tornieri (n = 60) and Leptopelis uluguruensis (n = 62) species were collected, humanely sacrificed, fixed in formalin, routinely processed, sectioned, stained with haematoxylin and eosin and analysed for diseases by histopathology. Disease prevalence (percentage) in P. Yakusini, N. Tornieri and L. uluguruensis were strongyloidiasis 23.3, 31.7 and 29%; chytridiomycosis 8.3, 38.3 and 11.3%; inflammatory reactions 13.3, 6.7 and 14.5%; viral inclusion bodies 15, 11.7 and 9.7%; and granuloma 0, 0 and 1.6%, respectively. It is concluded that there are potentially fatal disease conditions at Kihansi gorge and its surroundings that can threaten the life of the re-introduced KSTs. Keywords: Kihansi gorge, amphibians, Kihansi spray toad (KST), diseases, prevalence